Hydraulic tables and diagrams for practical engineers - Garrett, A. (Longmans, Green and Co., 1909)
Hydraulic projects demand many calculations, as every differing diameter and angle of pipe requires to be considered. These tables aim to reduce the labour of hydraulic calculations to the lowest possible limit consistent with the accuracy which is required for practical work.